Qualitative characteristics of functional readiness among female athletes of different sports qualification, who specialize in athlete all-round competitions - Chernova, T. S.; Aleksanyants, G. D. (The Russian Journal of Physical Education and Sport, 2017)
Functional potential of an organism among sportsmen is mainly conditioned by the following features: power, mobilization, efficiency and steadiness and they are considered the main characteristics of physiological systems activity, which determine and limit a high level of special sports physical working capacity, which is an integral index of functional readiness. Material. Comparative analysis of the development level of the main qualitative characteristics of functional readiness among female athletes of different qualification, who specialize in athlete all-round competitions. Research methods: scientific literature analysis and summarizing, testing, comparative analysis, methods of mathematical statistics. Results. For the set objective realization, the research work was held among two groups of female athletes, who specialize in athlete all-round competitions. At rest and in case of physical loads the indices, which reflect qualitative characteristics (functional qualities) - power, mobilization, efficiency and steadiness of organism functioning were determined. It was revealed that the parameters of morpho-functional power have bigger values among more qualified female athletes. At the same time, this advantage is not so significant and is within the range of 1,0 - 10,7%. It is shown, that the parameters, which reflect mobilization and utilization opportunities of an organism among the female athletes of different qualification on the average differed insignificantly in both groups of female athletes. At the same time, the indices of functional steadiness in the groups of female athletes of different qualification differed significantly: more qualified athletes validly exceeded qualified ones - to 9,0-14,3%. Also more significant and mainly statistically valid was the preponderance of the qualified female athletes concerning the indices of functional efficiency (to 6,4-16,4%). Conclusion. The received results lead to the conclusion that the level of the organism functional readiness in general (in integrative expression) and its different qualitative characteristics is considerably higher among highly-qualified female athletes, who specialize in athlete all-round competitions, in comparison to qualified ones. The greatest differences between highly-qualified and qualified female athletes are in the parameters of functional steadiness and functional efficiency.